HUBUNGAN GENETIK IBU, PERILAKU IBU, PEMBERIAN ASI DAN PERSEPSI IBU DENGAN OBESITAS PADA ANAK USIA 2-3 TAHUN DI PAUD DAN KELOMPOK BERMAIN DI KOTA YOGYAKARTA - , ERVINA SILVIANINGSIH NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Obesity is a worldwide health problem. Obesity can occur at any age, but is most common in the first year of life, the age of 5-6 years and in adolescence. The prevalence of obesity increased from year to year, both in the developed and developing countries. Genetic history of the parents, maternal behavior, feeding patterns, and the mother's perception can be factors that lead to obesity in children. Objective: To determine the relationship between maternal genetic, maternal behavior, breastfeeding, and maternal perceptions of obesity in children aged 2-3 years in early childhood and preschool in Yogyakarta. Methods: The study was cross-sectional with obesrvasional design. The population in this study were children aged 2-3 years and their mother in early childhood and preschool in the city of Yogyakarta. Total sample of 60 children aged 2-3 years and their mother, obtained by the method of sampling purposiv. Independent variable genetic history, maternal behavior, breastfeeding, and maternal perceptions. Dependent variable is child obesity. To determine the relationship between the variables studied analysis was performed using chi square. Results: Of 60 subjects were mostly children (86.7%) and mothers (51.7%) have no nutritional status obesity. The average frequency of meals and snacks â¤ 3 times per day and energy intake â¤ 85% RDA. The majority of respondents (58.3%) breastfeed the child â¥ 6 months. Most of the study subjects (71.7%) had a good perception. Results of chi square analyzes between the genetic mother, maternal behavior, and demonstrate the value of breastfeeding p> 0.05. While the results of chi-square analysis between maternal perception indicates p value <0.05. Conclusion: There is a significant relationship between perceptions of mothers with child obesity and there is no significant correlation between maternal genetic, maternal behavior, and breastfeeding with obese children aged 2-3 years in early childhood and preschool in the city of Yogyakarta.